The More You Know, the Less You Stress: Menstrual Health Literacy in Schools Reduces Menstruation-Related Stress and Increases Self-Efficacy for Very Young Adolescent Girls in Mexico - Long, Jeanne L.; Haver, Jacquelyn; Mendoza, Pamela; Vargas Kotasek, Selvia M. (Frontiers in Global Women's Health, 2022)
Improving the menstrual health literacy of girls and boys is a key strategy within a holistic framework of Save the Children's school health and comprehensive sexuality education programming. As menstrual health is an emerging area of study and programming, Save the Children continues to learn and adjust its interventions using program evaluations and rigorous monitoring. This paper will examine program-monitoring data from three cohorts, representing 47 public schools in Mexico City, Puebla, and Mérida, Mexico. The study focuses on female students in 5th and 6th grade who participated in We See Equal, a school-based program centered on gender equality and puberty education, between September 2018 and December 2019. This study used a cross-sectional quantitative cohort approach to document changes in girls' experiences and perceptions around managing menstruation in school. The analysis compares girls' knowledge and experiences before and after participation in We See Equal to understand how knowledge changes over the program and how those changes may contribute to menstruation-related school engagement, stress, and self-efficacy (MENSES) outcomes. Multivariate regression models explored relationships between MENSES outcomes, knowledge and socioeconomic status (SES). Overall, results show that the more knowledge girls acquired, the higher their self-efficacy score and the lower their stress score, however, certain MHH knowledge was more predictive of MENSES outcomes and varied by SES. Among girls from lower SES, we observed significant relationships between knowing what their period was prior to menarche and the three MENSES outcomes. Decreases in menstruation-related stress were driven by items related to the practical knowledge of how to dispose of sanitary pads and reduced feelings of nervousness on days they had their period at school. Increases in self-efficacy were primarily driven by girls' confidence in their ability to track their period from month to month, feelings that they could still do well on an exam if they had their period at school, and security that they could ask a friend to lend them a pad if they needed one. Implications for future menstrual health literacy programming and targeting populations for menstrual health education, as well as priorities for future research will be discussed.